Categorisation of sustainable-use protected areas for context-specific conservation initiatives in the Amazon - Leticia Lopes Dias; Angela Pellin; Neluce Soares; Pedro M. Pedro; Leticia Umbelina; Fabiana Prado (Parks, 2024)
Community conservation engages local actors and generates socio-economic gains that promote quality of life whilst protecting the territorial and biodiversity balance in protected areas. However, for conservation efforts of this nature to be effective, the territorial context in which they are situated must be understood and the management structure adequate. In this study, we analysed 134 protected areas that preserve biodiversity and cultural values in the Brazilian Amazon but vary in their management structures and are situated within different threat contexts. Here, we use a management-level indicator and a threat-based territorial context indicator (including deforestation, mining and fire) to classify areas and offer context-specific actions. Based on our classification, we recommend investing in protection and enforcement efforts in areas under greatest threat, as other initiatives will be at greater risk when carried out in these places. Protected areas with high management-level scores can foster innovative community conservation actions, whilst the most deficient ones require investment in basic instruments, such as management plans and the formalisation of management councils. We reinforce the need for comprehensive and up-to-date data on protected areas in the Amazon, especially regarding governance and local organisations, for more informed decision-making by funders, nongovernmental organisations and public authorities.